Revising the definition of vertical margin involvement following endoscopic polypectomy may reduce unnecessary surgery in patients with malignant colorectal polyps. Issue 3 (26th September 2019) - Richards, Colin; Kumarasinghe, Priyanthi; Hessamodini, Hannah; Waldron, Alice; Fernando, Diharah; Hodder, Rupert; Jacques, Angela; Raftopoulos, Spiro
Abstract : Background and Study Aims: Endoscopically resected malignant colorectal polyps (MCPs) present a dilemma regarding whether the risk of residual disease justifies a major bowel resection. Overtreatment is common, and the vast majority of patients who undergo resection have no residual tumor. The aim of this study was to investigate whether revising the definition of vertical margin involvement following MCP polypectomy could reduce unnecessary surgery. Patients and Methods: This was a cohort study of consecutive patients with MCPs treated at a tertiary hospital between 2004 and 2018. Data on demographics, index colonoscopy, polyp pathology, and any subsequent surgical resection were analyzed. Polypectomy resection margins were reviewed and measured to the nearest decimal place. The ability of existing guidelines (requiring a margin clearance of ≥ 1 mm) to predict residual disease was compared to a revised version requiring a margin clearance of ≥ 0.1 mm. Results: A total of 129 patients with an MCP were included. Of these 129 patients, 77 (60%) underwent surgical resection, of which 62 (81%) had no residual tumor. Existing guidelines, requiring a margin clearance of ≥ 1 mm, classified 28 patients as being at "low risk" for residual disease. Of these, four underwent surgery, but none had residual tumor ( P = 0.031). Revised guidelines, requiring a margin clearance of ≥ 0.1 mm, classified 44 patients as "low risk." Of these, in the 13 that had surgery, no residual tumor was found ( P = 0.003). Conclusions: Revising the definition of vertical margin involvement leads to more patients being correctly classified as being at low risk of residual disease. This has the potential to reduce unnecessary surgery in patients with MCPs. Abstract : This was a retrospective study looking at predictors of nodal metastasis in endoscopically removed polyps found to be malignant on histology. This study also challenges the current issue of margin status with regard to nodal risk of metastasis and highlights the potential morbidity, mortality, and cost savings when adopting a more modern approach to margin status.